Ecological control of mycotic pathogens in tomato crops - alternatives to synthetic pesticides - Alin DIN; Cristina MIHAESCU; Diana I. POPESCU (STEGARUS); Denisa VILCOCI; Georgiana CIRSTEA; Ionela-Daniela SARDARESCU; Diana Elena VIZITIU; Alina PAUNESCU; Ion MITREA; Rodi MITREA (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2023)
The pathogens Alternaria solani and Fusarium oxysporum f. sp. lycopersici are of significant interest from a pathogenic perspective in the context of tomato cultivation. This study focuses on evaluating the fungicidal and fungistatic effects of different synthetic substances and natural compounds on the development of these two investigated pathogens. The fungicidal agents employed comprised fosetyl aluminum at a concentration of 0.3%, azoxystrobin at 0.2%, and metiram at 0.3%, while the natural extracts investigated included those derived from European birthwort, celandine and sage, each tested at concentrations of 0.5%, 2%, 9%, and 15%. The assessment of mycelial growth inhibition was conducted utilizing Vincent’s formula. Additionally, the total polyphenol content (TPC) within the extracts was determined via the Folin-Ciocalteu spectrophotometric method in accordance with Frum et al. (2022). Furthermore, the antioxidant capacity of the extracts was evaluated using the DPPH radical scavenging method (2,2-diphenyl-1-picrylhydrazyl) and high-performance liquid chromatography (HPLC). Our research findings yielded noteworthy results, specifically, extracts derived from sage and celandine, particularly when present at a concentration of 15%, exhibited a fungistatic effect. This effect was particularly remarkable when compared to the performance of the synthetic fungicide azoxystrobin at a concentration of 0.2% when challenged with the Alternaria pathogen. These results suggest the potential utility of sage and celandine extracts as eco-friendly alternatives for mitigating fungal pathogens in tomato crops, warranting further investigation and consideration within agricultural practices.